The tax foreclosure meeting (Revista do Tribunal Regional Federal da 3ª Região, 2022)
This work aims to demonstrate that the tax execution meeting has advantages and can be determined ex officio by the judge.
Keywords: Power/duty to conduct the process; reasonable process duration; national policy for the appropriate treatment of conflicts